2018
DOI: 10.15252/emmm.201809355
|View full text |Cite
|
Sign up to set email alerts
|

A versatile drug delivery system targeting senescent cells

Abstract: Senescent cells accumulate in multiple aging‐associated diseases, and eliminating these cells has recently emerged as a promising therapeutic approach. Here, we take advantage of the high lysosomal β‐galactosidase activity of senescent cells to design a drug delivery system based on the encapsulation of drugs with galacto‐oligosaccharides. We show that gal‐encapsulated fluorophores are preferentially released within senescent cells in mice. In a model of chemotherapy‐induced senescence, gal‐encapsulated cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
199
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 247 publications
(228 citation statements)
references
References 65 publications
4
199
0
1
Order By: Relevance
“…In addition to cell labels, nanoparticles can encapsulate small molecules capable of killing senescent cells, potentially widening the therapeutic window of these agents ( and Fig ). Gal‐encapsulated doxorubicin, GalNP(dox), induced apoptosis in palbociclib‐induced senescent cells, but not in control (proliferative) cells, thus validating its therapeutic senescence‐targeting potential (Muñoz‐Espín et al , ). Of note, GalNP(dox) treatment restored lung function in mice with bleomycin‐induced pulmonary fibrosis and reduced the lung fibrotic scar.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition to cell labels, nanoparticles can encapsulate small molecules capable of killing senescent cells, potentially widening the therapeutic window of these agents ( and Fig ). Gal‐encapsulated doxorubicin, GalNP(dox), induced apoptosis in palbociclib‐induced senescent cells, but not in control (proliferative) cells, thus validating its therapeutic senescence‐targeting potential (Muñoz‐Espín et al , ). Of note, GalNP(dox) treatment restored lung function in mice with bleomycin‐induced pulmonary fibrosis and reduced the lung fibrotic scar.…”
Section: Introductionmentioning
confidence: 95%
“…One of the first methodologies to image and monitor senescence noninvasively in vivo was based on a sequential reporterenzyme bioluminescence technology to track b-gal activity by using Lugal, a caged galactoside-luciferin conjugate (Wehrman et al, 2006). Recent studies validated the use of nanoparticles and fluorescent probes to target senescent cells in mouse models (Lozano-Torres et al, 2017;Muñoz-Espín et al, 2018;Wang et al, 2019). Nanoparticles open up the possibility of encapsulating tracers and contrast agents for the imaging of senescence location and burden, and to be used as imaging biomarkers to direct promising therapies to populations most likely to benefit from them.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the potential to harness the elevated b-galactosidase activity of senescent cells have been exploited with galacto-oligosaccharide encapsulated nanoparticles (GalNP) (Agostini et al 2012). Combination of GalNP with different cargoes offers flexibility to image or eliminate senescent cells (Munoz-Espin et al 2018). However, this flexibility comes to the expense of having to use a modular system, comprised of both the GalNP and the cargo.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that galacto-oligosacharide encapsulated nanoparticles (GalNP) preferentially release their content on senescent cells (Agostini et al 2012). Consequently, this GalNP can be used in combination with different cargos to either image or kill senescent cells (Munoz-Espin et al 2018).…”
Section: Introductionmentioning
confidence: 99%